Penyuluh Agama Islam, Religiusitas, dan Salatiga sebagai Kota Toleran - Sholahuddin; Zaenal Abidin Eko Putro (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2020)
[ISLAMIC INSTRUCTORS, RELIGIOSITY, AND SALATIGA AS TOLERANT CITY]. Developing and strengthening a religiously motivated society lies in the responsibility of the Islamic religious instructors including those who work for the Ministry of Religious Affairs (MoRA) of Salatiga City, Central Java. Their detailed tasks have been released, that is in accordance with the Decree of the Director General of Islamic Community Guidance No. 298 of 2017 concerning Guidelines for Islamic Extension Workers, namely 8 (eight) specific fields which are the following; Read and Write the Qur'an, halal products, radicalism, and Islamic splinter group, sakinah families, HIV/AIDS & Drugs, Zakat, Waqf, and Religious Harmony. In addition, it is widely known that Salatiga has been granted as the most tolerant city in Indonesia by the Setara Institute for the last several years. Currently, the role of religious instructors to fulfill their assignments to support such a tolerant city remains less unknown. This article that is stemmed from the qualitative research has shown that religious instructors of the Islam section in Salatiga are able to fulfill their role as the contributor for religiosity and harmony in society, although some challenges remain. They could also accelerate with the title of tolerant city that pinned to their city.